Safety and nutritional value of a dried killed bacterial biomass from Escherichia coli (FERM BP‐10941) (PL73 (LM)) as a feed material for pigs, ruminants and salmonids. (30th August 2017) - ; Rychen, Guido; Aquilina, Gabriele; Azimonti, Giovanna; Bampidis, Vasileios; Bastos, Maria de Lourdes; Bories, Georges; Cocconcelli, Pier Sandro; Flachowsky, Gerhard; Gropp, Jürgen; Kolar, Boris; Kouba, Maryline; et al.
Abstract: PL73 (LM) is a dried, heat‐inactivated bacterial biomass used as a feed material produced from an Escherichia coli K‐12 strain, which was genetically modified to overproduce lysine. The recipient organism E. coli K‐12S B‐7 is considered to be safe. The traits introduced in the final modified strain E. coli FERM BP‐10941 are mainly limited to the overproduction of lysine. No full‐length antibiotic resistance genes or other sequences of concern remain in the modified strain. In conclusion, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) does not identify risks for human and animal health or the environment from the biomass regarding the genetic modification of the strain. Although considering the zootechnical end‐points only, the maximum safe level for dairy cows would be 6% PL73 (LM) of feed dry matter ( 5% in complete feed) and for pigs for fattening up to 6% PL73 (LM), the unexplained effects on blood coagulation, on plasma lipoproteins in dairy cows and on total plasma bilirubin and liver weight in pigs prevent a clear conclusion of safe dietary levels for ruminants and pigs for fattening. PL73 (LM) is safe for salmonids up to a dietary concentration of 13%. The toxicological data indicate adverse effects of PL73 (LM) on blood coagulation and liver, which also occur in target species. As a consequence, the FEEDAP Panel is unable to conclude on the safety for the consumer of products derived from animals receiving feed containing PL73 (LM). PL73 (LM) is not considered a skin/eye irritant but should be considered as a potential skin and respiratory sensitiser. Moreover, any exposure of users to dust from the product via the inhalation route should be considered a serious risk. The FEEDAP Panel considers that substitution of PL73 (LM) for other protein‐rich feed materials will not adversely affect the environment.